Pola Asuh Ibu Rumah Tangga Karier Dalam Penerapan Nilai-Nilai Pendidikan Ekonomi Pada Anak Di Lingkungan Keluarga - Enno Febri Yustiko; Syahrul Munir (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
This study aims to determine the parenting pattern of career housewives in the application of economic education values to children in the family environment. This study uses a qualitative approach using a phenomenological type of research. The subject of this research is a career housewife who works at PT. Gudang Garam Tbk who has children who live in RT 04 RW 16 Dusun Tepus, Sukorejo Village, Ngasem District, Kediri Regency because researchers know that in that area the majority of mothers work as employees of PT. Gudang Garam Tbk. Based on the results of interviews conducted on career housewives who have children, it is known that career housewives apply democratic parenting in the application of educational values to children, democratic parenting is very suitable to be applied by career housewives because this parenting provides more discussion approach, listening to children's complaints, providing feedback, good communication and not being rigid in applying educational values to children, so that children can have effective and efficient economic characteristics.DOI: https://dx.doi.org/10.17977/UM014v15i12022p022